A VALIDATED STABILITY INDICATING RP-HPLC METHOD FOR ESTIMATION OF AVAPRITINIB IN BULK AND TABLET DOSAGE FORM - MISHRA, SUVASISH; SARKER, KOUSHIK; GHOSH, AVIJIT; SAHA, ABHIJIT; SEN, SUBRATA (International Journal of Applied Pharmaceutics, 2022)
Objective: The present investigation aims to develop a simple, cost effective, and reliable stability-indicating RP-HPLC assay method for analysis of avapritinib in bulk and the tablet dosage form. Methods: The method was developed using Acetonitrile and Methanol in a ratio of 70:30 (v/v) as the mobile phase, flowing at a rate of 1 ml/min, in an isocratic mode. A reverse phase column (Symmetry C18 column, 250 mm x 4.6 mm, 5 µm) was used as the stationary phase. The detection of the compound was made using a UV detector set at 245 nm. The validation and force degradation studies of the method were done following the International Conference on Harmonization (ICH) guidelines. Results: The method was validated using the prescribed parameters like system suitability, LOD, LOQ, accuracy, precision, robustness, specificity etc. The relative standard deviation (% RSD) of the peak area observed in each case was found within the accepted range (< 2%). The tailing factor and the plate count were found to be less than 2 and more than 2000 respectively in each observation. The coefficient of correlation (r2) value in the linearity study was found to be 0.9997. The drug was found to be quantified accurately in presence of its degraded products. Conclusion: The developed simple and economic method is a suitable option for the qualitative and quantitative study of avapritinib in bulk and tablets even in presence of its degraded products which may arise because of oxidation, hydrolysis, thermal and photolytic decomposition.